IMPROVING TEACHERS’ PERFORMANCE THROUGH THE HEADMASTERS’ TRANSFORMATIONAL LEADERSHIP AND MOTIVATION AT PUBLIC ELEMENTARY SCHOOLS - Harkati Harkati; Sukirman Sukirman; Gunawan Setiadi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
The purpose of this study was to analyze the effect of the headmasters’ transformational leadership on teachers’ performance, the effect of motivation on teachers’ performance, and the influence of the headmasters’ transformational leadership and motivation in multiple ways on teachers’ performance. This research was conducted at public Elementary Schools in Kecamatan Tayu, Kabupaten Pati. The type of research was quantitative research through correlation . The number of samples in this study was 144 respondents. The data were collected by giving a questionnaire to the teachers. Then, the data were analyzed by testing the validity and reliability, and through classic assumption tests and multiple linear tests which were processed by using IBM SPSS 24. The results showed the following: (1) Transformational leadership of the headmasters (X1) was proven to have a significant effect on teachers’ performance at public Elementary Schools in Kecamatan Tayu, Kabupaten Pati; (2) Work motivation (X2) was proven to have a significant effect on teachers’ performance in public Elementary Schools in Kecamatan Tayu, Kabupaten Pati; and (3) Transformational leadership of the headmasters and work motivation and compensation simultaneously proved to have a significant effect on teachers’ performance at public Elementary Schools in KecamatanTayu, Kabupaten Pati for as much as 77.6%.